Histone‐deacetylase 8 drives the immune response and the growth of glioma. Issue 11 (26th July 2021) - Mormino, Alessandro; Cocozza, Germana; Fontemaggi, Giulia; Valente, Sergio; Esposito, Vincenzo; Santoro, Antonio; Bernardini, Giovanni; Santoni, Angela; Fazi, Francesco; Mai, Antonello; Limatola, Cristina; Garofalo, Stefano
Abstract: Many epigenetic modifications occur in glioma, in particular the histone‐deacetylase class proteins play a pivotal role in glioma development, driving the proliferation rate and the invasiveness of tumor cells, and modulating the tumor microenvironment. In this study, we evaluated the role of the histone deacetylase HDAC8 in the regulation of the immune response in glioma and tumor growth. We found that inhibition of HDAC8 by the specific inhibitor PCI‐34051 reduces tumor volume in glioma mouse models. We reported that HDAC8 modulates the viability and the migration of human and murine glioma cells. Interestingly, HDAC8 inhibition increases the acetylation of alpha‐tubulin, suggesting this epigenetic modification controls glioma migration. Furthermore, we identify HDAC8 as a key molecule that supports a poorly immunogenic tumor microenvironment, modulating microglial phenotype and regulating the gene transcription of NKG2D ligands that trigger the Natural Killer cell‐mediated cytotoxicity of tumor cells. Altogether, these results identify HDAC8 as a key actor in glioma growth and tumor microenvironment, and pave the way to a better knowledge of the molecular mechanisms of immune escape in glioma. Main Points: HDAC8 modulates the viability of human and murine glioma cells and tumor migration through a–tubulin acetylation. HDAC8 supports a poorly immunogenic tumor microenvironment modulating microglial phenotype and inhibiting NK cell cytotoxic activity.